2020
DOI: 10.1007/s00276-020-02511-w
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional computed tomography angiography study of the anatomy of the accessory middle colic artery and implications for colorectal cancer surgery

Abstract: Purpose In the present study, we focused on the accessory middle colic artery and aimed to increase the safety and curative value of colorectal cancer surgery by investigating the artery course and branching patterns. Methods We included 143 cases (mean age, 70.4 ± 11.2 years; 86 males) that had undergone surgery for neoplastic large intestinal lesions at the First Department of Surgery at Yamagata University Hospital between August 2015 and July 2018. We constructed three-dimensional (3D) computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The frequency of the aMCA presence reported in the literature is highly variable. It ranges from 4.1% [ 13 ] to 49.2% [ 16 ]. It seems that the reported incidence of finding this vessel has increased during the last three decades [ 14 ], reflecting the rising interest in this vessel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of the aMCA presence reported in the literature is highly variable. It ranges from 4.1% [ 13 ] to 49.2% [ 16 ]. It seems that the reported incidence of finding this vessel has increased during the last three decades [ 14 ], reflecting the rising interest in this vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Further, when preoperative examinations suggest aMCA following IMV, one should anticipate a vessel in close proximity to the inferior border of the pancreas which has a high probability of being accompanied by lymphatic drainage from the splenic flexure. In addition, it is necessary to mention when the aMCA is in concern that considerable confusion can arise due the different nomenclature deployed in the literature for a vessel with a similar origin and trajectory, the superior left colic artery [ 42 ], the left accessory aberrant colic artery [ 32 , 43 ], accessory left colic artery [ 13 , 44 ] or most recently the transverse colon splenic flexure artery [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 16 studies (n = 2203 patients) were included [3,7,8,[14][15][16][17][18][19][20][21][22][23][24][25][26]. Most of the studies were performed in Asia (12 studies, 1923 patients) while the rest were from North America (2 studies, 240 patients); Europe (1 study, 13 patients) and the Middle East (1 study, 27 patients).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The analysis of the frequency of the AMCA has been reported. (13)(14)(15)(16)) Some studies focused on the splenic exure and its relationship to the left colic artery. (34,35) The analytical methods have been reported, with some studies using CT angiography and others using cadavers; the AMCA was reported to be present in 6.8-49.2%.…”
Section: Discussionmentioning
confidence: 99%